MANAJEMEN EKSTRAKURIKULER GERAKAN PRAMUKA DALAM MENGEMBANGKAN KARAKTER KEPEMIMPINAN SISWA DI MADRASAH ALIYAH - Fadlilah, Fadlilah; Chaniago, Fransisko; Fitriani, Suci; Mustar, Mustar; Febriyana, Nurul (STKIP Pesisir Selatan, 2025)
Extracurricular management of the Scout Movement in developing student leadership character is part of education in madrasah, which also supports the goals of national education to develop student character. The purpose of this research is to explain how the extracurricular Scout Movement is managed in its role in developing student leadership character at Madrasah Aliyah Riyadhul Jannah Tanjung Jabung Barat. This research uses a qualitative descriptive approach, collecting data through observation, interviews and documentation. The results of this study indicate that the extracurricular management of the Scout Movement that is applied uses four management functions, namely planning, organizing, implementing, and evaluating, which in its application continues to be maximized. The implementation of the extracurricular scout movement is carried out by coaching and habituation, the results of which have an impact on students to be able to apply it in their daily lives. activities carried out include routine training which includes a buffer system, marching, basic leadership training, wandering and so on, so that students are able to dare to appear in public, lead and work well in teams, and have better ethics and manners, and from these scouting activities directly or indirectly the leadership character of students can develop well.